Cultural heritage of Vaie community: Engulfed cultural heritage of minor ethnic groups by other larger ethnic groups - Fatin Hana Naning, Mohamad Maulana Magiman, Rahimah Jamaluddin, Ahmad Nasir Mohd Yusoff,; Tze Jin Wong, Lee Feng Koo & (Opción)
This ethnographic study focus to explore the uniqueness of Vaie community cultural heritage and differences between Vaie and Melanau communities. The main approach used ethnographic, descriptive, and comparative analysis. Observation and semi-structured individual and group interview on history of Vaie community was done by involving ten (10) respective respondents. Findings of this study suggest that Vaie ethnicity are native people of Bintulu and are completely different from Melanau or any other ethnicity in Sarawak as a whole. It is recommended that the Department of Statistics, Malaysia should provide options for the minority ethnic groups especially that of Vaie in Bintulu in other to follow its population growth.